Evaluation on empirical models for the prediction of cyclone efficiency - Jolius, Gimbun; Chuah, Luqman Abdullah, Assoc. Prof. Dr.; Choong Thomas, Thomas Shean Yaw, Assoc. Prof. Dr. Ir.; Fakhru’l-Razi, Ahmadun, Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/